PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA SMARTPHONE SAMSUNG DI MEGASTORE SURABAYA - Mia Anggraini Eka Putri; Supriyono Supriyono (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The current study was conducted to identify how much influence product quality and brand image have on purchasing decisions for Samsung smartphones at Megastore Pakuwon Mall Surabaya. This study explains the relationship between independent variables, namely product quality and brand image with purchasing decisions as the dependent variable. This research is currently being conducted using quantitative methods with a sample size of 55 people. The distribution of statements to the samples is assisted through Google Forms software. How to collect samples using non-probability sampling with purposive sampling method. Sampling was based on samples who had purchased a Samsung smartphone at Megastore Pakuwon Mall Surabaya and were aged 17 years and over. With the data obtained from the results of filling out the statement form, research will be carried out using analytical techniques using the SEM (Structural Equation Model) method on a component basis using Partial Least Square (PLS). The results of data processing in the current study can be concluded that the purchase decision of Samsung smartphones is positively and significantly influenced by the variables of product quality and brand image